Pediatric palliative care in Brazil: reflections on end of life based on geographic mapping - Esther Angélica Luiz Ferreira; Leandro Saito; Maycon Rodrigo Sarracini; Cristina Helena Bruno; Augustus Relo Mattos; Cristina Ortiz Sobrinho Valete; Rodrigo Bezerra de Menezes Reiff (Springer, 2024)
Abstract Introduction In Brazil, a country of continental dimensions, the lack of services in the different regions is a major barrier that prevents patients from accessing Pediatric Palliative Care (PPC). If accessing PPC is already challenging, end-of-life care for these patients may also be difficult. Therefore, this study is based on a recent mapping effort, aimed at reflecting on the end-of-life care for children in Palliative Care in Brazil. Method Descriptive, cross-sectional study, and online survey research, based on a larger study of Palliative Care Network. Results The final sample comprised 90 Pediatric Palliative Care services, which proved to be unevenly distributed across the country. Many services lack a minimum team, 40% face difficulties accessing opioids, and one-third do not provide bereavement care. Discussion There should be more services with better distribution across the country, and a minimum team should be required to provide adequate care for children and adolescents. Strategies to improve symptom control and grief support should be introduced. Conclusions It is concluded that continuing education and the inclusion of relevant topics in health courses are necessary. Additionally, health service managers must expand their focus to address these issues effectively.